2018
DOI: 10.1016/j.omtn.2018.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of a Single N-Glycosylation Site in Human FSTL 1 Induces Cardiomyocyte Proliferation and Cardiac Regeneration

Abstract: Adult mammalian hearts have a very limited regeneration capacity, due largely to a lack of cardiomyocyte (CM) proliferation. It was recently reported that epicardial, but not myocardial, follistatin-like 1 (Fstl1) activates CM proliferation and cardiac regeneration after myocardial infarction (MI). Furthermore, bacterially synthesized human FSTL 1 (hFSTL1) was found to induce CM proliferation, whereas hFSTL1 synthesized in mammals did not, suggesting that post-translational modifications (e.g., glycosylation) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 43 publications
2
55
0
Order By: Relevance
“…The biological function of FSTL1 is closely related to its posttranslational modification by N-linked glycosylation [36,37]. Consistent with the enrichment of the glycosylated FSTL1 in BAT (Fig.…”
Section: Glycosylation Was Essential For the Biological Function Of Fsupporting
confidence: 79%
See 1 more Smart Citation
“…The biological function of FSTL1 is closely related to its posttranslational modification by N-linked glycosylation [36,37]. Consistent with the enrichment of the glycosylated FSTL1 in BAT (Fig.…”
Section: Glycosylation Was Essential For the Biological Function Of Fsupporting
confidence: 79%
“…In mouse FSTL1, three potential sites for N-glycosylation and two for O-glycosylation are present. An in vitro study has shown that only the three aspartate residues Asp 142 , Asp 173 , and Asp 178 are Nglycosylated and show cell-type specificity [36]. In our study, we found that FSTL1 in brown fat cells is highly glycosylated.…”
Section: Discussionsupporting
confidence: 60%
“…Collectively, our data are primary in linking, within a human model, the benefit of allogeneic stem/progenitor-based therapy to the activity of EV/Exs secreted by therapeutic cells. Resident cardiac stem/progenitor cells and cardiomyocytes are critical not only for tissue homeostasis and renewal of cardiomyocyte pool [39], but also for organ regeneration and/or repair after cardiac injury [40][41][42]. The rapid internalization of EV/Exs by allogeneic hCPC and cardiomyocytes, which represented in situ resident myocytes in our in vitro model, promoted both migration and proliferation.…”
Section: Discussionmentioning
confidence: 92%
“… 57 EGFP, mCherry, Fluc modRNA delivery optimization optimal modRNA expression in heart alginate, nanomaterial encapsulated mice and pig 11 Magadum et al. 48 mutated FSTL1 ablation of N180Q, N-glycosylation site of hFSTL1 by modRNA delivery increased CM proliferation, improved cardiac output, and reduced scar size post-MI CM proliferation, decreased scar size, improved heart function sucrose-citrate buffer mice …”
Section: Main Textmentioning
confidence: 99%